Effective Downsizing in Small-to-Medium Sized UAE based Organization - Shalabi, Amal (2009)
The downsizing issue is a topic of interest especially for all organizations experiencing financial decline. In general terms, Downsizing is defined as the set of activities carried out by management to enhance the efficiency, productivity, and competitiveness of the organization by reducing the workforce size. The research provides an opportunity to understand the growing phenomenon of downsizing. The purpose of this research is to give a better understanding of what are important factors to consider during downsizing. The selected case study resembles a sample of the mid sized organizations in UAE and primary data was collected through personal interviews with the employees. The research critically studies different aspects of downsizing process at organization “ABC”. Where “ABC” is a small to medium size national organization in UAE working in the service sector in UAE and recently has gone through a downsizing process due to the economic down-turn. The research also assesses employees’ perception of organizational downsizing across mainly two dimensions: the degree to which the downsizing process was effective and the degree to which it impacted the organization overall performance as well as employees’ productivity and morale. A particular interest in this research was to review the downsizing process at “ABC” with respect to the successful factors for effective downsizing compiled by Cameron in 1994.